The influence of demographic characteristics of consumers on decisions to purchase technical products - Puška, Adis; Stojanović, Ilija; Šadić, Sead; Bečić, Haris (The European Journal of Applied Economics, 2018)
The term consumer behavior has become very popular in recent studies.It is characterized by various processes, with consumers purchasingdecisions being one of them. This paper explores the way in whichdemographic characteristics influence purchasing decisions with focuson technical products including household appliances, computers, TVsets and similar technical products that cost more than 400 BAM. Theempirical study was conducted in the region of northeast of Bosnia Herzegovinaand 192 respondents were included in the study to express theirallegations of purchasing decisions. Factor analysis was used to identifybroader constructors as a basis for observation of the variables. In total,six variables were identified. Based on the calculation of Cronbach'sAlpha indicators, it has been established that there was a low internalaffiliation of claims in two variables, upon what they were discarded.Thus, four variables were used to study purchasing decision-making.The results of multivariate analysis of variance (MANOVA) showedthat gender, income level and employment status of the respondentssignificantly influence purchasing decisions among consumers. Theanalysis of variance (ANOVA) has further shown that females Underthe age of 25 and whose income is less than 400 BAM with less than 25years are generally dedicating to purchasing decisions. The empiricalfindings showed that the most satisfied with their purchasing decisionsare male respondents, whose income varies between 400 BAM and800 BAM and who belong to the category of students under 25 years.